Educar en derechos humanos: una tarea urgente (2012)
This article is the result of a conceptual review of the thesis on Master of Education: Human Development, and collects the most important theoretical elements of the exercise of human rights education, which has become an urgent task for professional educators and has transcended various spaces in which individuals continuously interact. For this reason, as educators, we must not postpone the role of human rights education.